2006
DOI: 10.1098/rspb.2006.3743
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected heterozygosity in an island mouflon population founded by a single pair of individuals

Abstract: In population and conservation genetics, there is an overwhelming body of evidence that genetic diversity is lost over time in small populations. This idea has been supported by comparative studies showing that small populations have lower diversity than large populations. However, longitudinal studies reporting a decline in genetic diversity throughout the whole history of a given wild population are much less common. Here, we analysed changes in heterozygosity over time in an insular mouflon (Ovis aries) pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
85
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 34 publications
4
85
0
Order By: Relevance
“…Given that random terms were not significant in the multivariate mixed model (table 3), we used sample size to give observations of different weights in a weighted least-squares analysis (e.g. Kaeuffer et al 2007;Ortego et al 2007c). As above, average colony heterozygosity was negatively associated with squared distance to the nearest colony of the lesser kestrels (H O : tZK3.521, pZ0.001; HL: tZ3.190, pZ0.002) and positively associated with colony size (H O : tZ3.521, pZ0.001; HL: tZK2.753, pZ0.008).…”
Section: Results (A) Patterns Of Immigrationmentioning
confidence: 99%
“…Given that random terms were not significant in the multivariate mixed model (table 3), we used sample size to give observations of different weights in a weighted least-squares analysis (e.g. Kaeuffer et al 2007;Ortego et al 2007c). As above, average colony heterozygosity was negatively associated with squared distance to the nearest colony of the lesser kestrels (H O : tZK3.521, pZ0.001; HL: tZ3.190, pZ0.002) and positively associated with colony size (H O : tZ3.521, pZ0.001; HL: tZK2.753, pZ0.008).…”
Section: Results (A) Patterns Of Immigrationmentioning
confidence: 99%
“…Similarly, Kaeuffer et al. (2007) revealed a higher than expected heterozygosity in another introduced mouflon population. Contrary to heterozygosity, allelic richness values in the study population were closer to those observed in the Cyprus population (see Supplementary Material F, Tables S5 and S6).…”
Section: Discussionmentioning
confidence: 74%
“…In closed populations, N a can only be restored by mutations; heterozygosity is thus expected to be restored faster and to be easier to save than N a when conditions are favorable. In our population, founders from three different origins (Table 1) were released on four occasions, and growth rate after introduction is thought to have been as high as in other introduced mouflon populations (e.g., Kaeuffer et al., 2007) and most herbivore populations (Forsyth & Caley, 2006). These conditions could thus have favored heterozygosity maintenance at a relatively high level, comparable to unbottlenecked populations, while allelic richness still bears the scars of the founder events.…”
Section: Discussionmentioning
confidence: 99%
“…The latter occurs because individuals within the population vary in their inbreeding levels. Kaeuffer et al (2006) suggest that their results are more likely to be due to local than general effects, but admit that there is no concrete way to test this. The inability to discriminate between these two hypotheses is not, in my opinion, of great concern as ultimately all genome-wide effects must have a local cause.…”
mentioning
confidence: 99%
“…This is of particular concern with regard to the conservation of endangered species of plants and animals, as the loss of genetic diversity through random genetic drift can compromise the future ability of populations to evolve in the face of changing environmental conditions. Thus, a recent paper published in the Proceedings of the Royal Society B (Kaeuffer et al, 2006) demonstrating that an isolated population of mouflon (Ovis aries) introduced to a remote island as a single founding male-female pair, has apparently increased in heterozygosity (a measure of genetic variation) over the course of approximately 23 generations is of great interest. Kaeuffer et al (2006) suggest that this increase in heterozygosity is due to natural selection acting against inbred individuals.…”
mentioning
confidence: 99%